Copyright Law and Metaverse: A Comparative Study of Challenges and Opportunities of the Egyptian Copyright Law Entering The Virtual Era - Khalaf, Ayat (AUC Knowledge Fountain, 2025)
Metaverse invokes legal challenges of Intellectual Property Rights in a limitless world of imagination for both entertainment and business aspects. The virtual world requires special devices and technologies to be accessed such as VR (virtual reality) and AR (augmented reality) appliances. The creation and protection of these devices cannot operate without patents. Besides, the protection of their software and platforms goes through copyright protection. Moreover, this imposes a non-traditional sense of trademark protection for new categories of goods and services. The peculiarities of copyright in the metaverse lie in two main challenges: firstly, copyright in the virtual world is usually discussed under an exceptional dogma such as the fair use doctrine and the first sale doctrine which cannot extend to include all the emerging legal questions under the traditional view of copyright. Secondly, the human centralized view of copyright in most cases hinders non-human creativity from the protection of copyrights. This is manifested in discussing the copyrightability of NFTs that are totally created and circulated virtually. The matter becomes more complicated in the Latin law schools which maximize the human role in the creative work to amount to be copyrighted. The current discussions spark debates over the legal issues of copyrights in the virtual worlds but have not amounted yet to form a general theory of virtual copyright. Thus, this research investigates the current challenges of the comparative copyright laws through an analytical lens of the comparative judicial precedents in anticipation of diagnosing the opportunities for the Egyptian Copyright Law to enter the virtual era.